A Compendium of Pattern recognition techniques in face, speech and lie detection (2015)
Lie is a false statement made with deliberate intent to deceive, this is intentional untruth. People use different technologies of lie detection as Pattern recognition is a science to discover if an individual is telling the truth or lying. Patterns can describe some characteristics of liars, in this work to face and speech specifically. Face recognition take patttern of face and speech recognition of voice or speech to text. So this paper pretends realize a compendium on lie detection techniques and pattern recognition face and speech. It permits to review the actual state of the tecnhologies realized in these recognitions. Also It presents an analysis of tecnhologies using some of these techniques to resum the result. Keywords: Pattern recognition, facial recognition, speech recognition, lie detection, digital image processing